Identifikasi Model dari Pesawat Udara Tanpa Awak Sayap Tetap Jenis Bixler - Abdul Majid; Raden Sumiharto; Setyawan Bekti Wibisono (IJEIS (Indonesian Journal of Electronics and Instrumentation Systems), 2015)
Flight model is one of importing thing in fixed-wing unmanned aerial vehicle (UAV) control system development, mainly in the aircraft autopilot. Through this flight model, the aircraft motion can be represented and simulated.In this research, the flight model is obtained through system identification and system modelling of Bixler fixed-wing  unmanned aerial vehicle. System identification is based on experiment data and use state-space model structure. There are three stages in this research, aircraft motion system modelling, flight data collecting, and flight model identification. Through those three stages, Bixler fixed-wing unmanned aerial vehicle flight model is obtained as represented in two modes, longitudinal mode and lateral modeThe Bixler fixed-wing unmanned aerial vehicle longitudinal mode flight model is obtained using 13 parameters. The lateral mode is obtained using 11 parameters. All modes are in 4th order state space model structure.